Critical analysis on present status of hand loom industries in Jaffna district - Aroosiya Banu, M.S.; Kularajasingam, P.; Nithilavarnan, A. (South Eastern University of Sri Lanka, 2022)
The traditional handloom weaving industry forms the basis of the garment industry, which is defined as the second skin of human. This handloom weaving industry is having low production cost, low capital, and eco-friendliness cottage industry. The handloom industry itself is an industry with a large number of handloom-based job opportunities and a large workforce. The study was conducted as a direct field study to focus on the handloom industry in the Jaffna district. The main objective of the study is to examine the problems currently faced by the handloom industry in the Jaffna district. During the study the entire population of the study area was considered and data was collected. The primary level and secondary level data, obtained from the study are analyzed through quantitative and qualitative data analysis methods and the results are obtained. The results obtained are reported and described through tables and diagrams. The study consists of five parts. They are Introduction to the study, literature review, study methodology, discussion, decisions and recommendations. Discussion of the study analyzed the problems faced by the handloom industry in the Jaffna district, the changes in the handloom industry in the Jaffna district after the end of the war, and the creation of Handloom based employment opportunities in the Jaffna district. Most of the problems can be solved by the following recommendations. They are new facilities like transport offers and employees provident fund to satisfy handloom weavers, develop the weaving skills of handloom weavers, supply of looms, machinery for handloom weaving to encourage handloom weavers in Jaffna District, provide appointments for loom teachers, completion of infrastructure facilities for handloom weaving mills, enhancing safety of production stations, teach handloom weaving course as a technical subject in Sri Lankan education system, implementation of a proposal for government servants to wear handloom weaving garments at least once a week and merging the handloom weaving mills located in the Jaffna district into one company.
Keywords: Handloom Weaving; Jaffna; Employee; Cottage Industry; Ecology